Cultural Da'wah in The Millenial Era: Studi on Wayangaji Ki Miko Cakcoy - Nurrohmah, Shinta; Putra, Robby Aditya; Khadiq, Khadiq (AJIS: Academic Journal of Islamic Studies, 2023)
Islamic da'wah or Islamization on the island of Java was first carried out by the nine saints called walisongo, among those who were phenomenal with Javanese culture such as wayang kulit was Sunan Kalijaga. The da'wah that was carried out was considered effective and efficient so that it was able to make Javanese people a Muslim majority, this was because the concept of da'wah which carried Javanese Sufism until it was adopted in the millennial era as carried out by Ki Miko Cakcoy. The nuances of local wisdom that are still maintained as glue between relationships between people in the current millennial era are the big homework of a da'I in society. Therefore, the purpose of this study is to examine the cultural da'wah strategies carried out by Ki Miko Cakcoy in preaching in the midst of millennial modernity. The research method used in writing this article is descriptive qualitative with data collection through interviews, observation and documentation. The results of this study indicate that cultural da'wah in the millennial era is needed so that it can become an adaptive da'wah model without diluting cultural arts values as a legacy of local wisdom. The hope is that in the future cultural da'wah by raising local wisdom still needs to be carried out by other millennial preachers so that future generations do not easily forget the history that existed.